Cervical Cancer Profile in dr. Cipto Mangunkusumo Hospital Year 2013 - Soehartati Argadikoesoema Gondhowiardjo; Adji Kusumadjati; Prasetya Wibisono; Sri Mutya Sekarutami (Radioterapi & Onkologi Indonesia, 2019)
Background: Cervical cancer ranks in the second place based on the malignancy among female sex in Indonesia with a prevalence of 14.4% and a mortality rate of 10.3%. Hospital-Based Cancer Registry (HBCR) is a system of cancer registration in a hospital that can provide information about the general information of cancer patients, treatment, and outcome of treatment. This study was conducted to obtain the profile of cervical cancer in dr. Cipto Mangunkusumo general hospital (RSCM) in 2013 based on data from HBCR RSCM.Methods: The study was conducted by extracting the epidemiological data and cervical tumor data from HBCR RSCM in 2013 which was then analyzed descriptively.Results: The result showed that cervical cancer ranks at the second place from all the malignancy at RSCM (12%, n= 678), with domicile mostly come from outside Jakarta (52.8%, n = 358). The average age of cervical cancer was 49.48 years, the most common occurs in the age range 45-49 years. In terms of histopathology, squamous cell carcinoma is the most prevalent type of histopathology (74.2%, n = 447). The surgery is a type of action that done for early-stage cervical cancer (83,3%, n = 25), whereas the action of radiation is mostly done in locally advanced cervical cancer (79,9%, n = 273).Conclusion: Nevertheless, cervical cancer has a significant health burden in Dr. Cipto Mangunkusumo general hospital which is needed further management.